The Influence of Regulation on Trust and Risk Preference in Sharing Communities - Marth, Sarah; Sabitzer, Thomas; Hofmann, Eva; Hartl, Barbara; Penz, Elfriede (Frontiers in Psychology, 2020)
Sharing within communities has gained popularity in recent years. However, taking part in a community also comes with a certain amount of risk. This perceived amount of risk can be contained by regulations within a community as well as by potential participants’ trust in the community and the other members. We argue for a relation between regulation and the willingness to take the risk of joining a sharing community with trust as mediator. Thereby, we distinguish between two kinds of regulation (soft and harsh regulation) and two kinds of trust (implicit and reason-based trust) on two different levels (vertical and horizontal trust). In one laboratory and one online experiment with overall 432 participants, we found that the compound of high soft and low harsh regulation increases participants’ willingness to take the risk of participation and the effect of soft regulation is mediated mainly by vertical and horizontal reason-based trust. Based on our results, we encourage sharing communities to count on soft regulation in order to increase potential members’ trust in the community and therefore take the risk to participate.